2020
DOI: 10.1007/s10461-020-02894-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Impact of COVID-19 on Men Who Have Sex with Men Across the United States in April, 2020

Abstract: The COVID-19 pandemic is reinforcing health inequities among vulnerable populations, including men who have sex with men (MSM). We conducted a rapid online survey (April 2 to April 13, 2020) of COVID-19 related impacts on the sexual health of 1051 US MSM. Many participants had adverse impacts to general wellbeing, social interactions, money, food, drug use and alcohol consumption. Half had fewer sex partners and most had no change in condom access or use. Some reported challenges in accessing HIV testing, prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
505
3
14

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(559 citation statements)
references
References 4 publications
37
505
3
14
Order By: Relevance
“…Additionally, it is incorrect to assume a diminished sexual risk for HIV, among gay men and other MSM, especially for men in sero-different domestic partnerships or men who are employed as sex workers (31,40). New data from the U.S. has not only reinforced this point but also underscored the ongoing need for uninterrupted access to HIV prevention tools gay men and other MSM may need (13). Otherwise, consequences of the reductions in HIV prevention tools can potentially be catastrophic in the HIV prevention response, particularly if they are not reversed (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is incorrect to assume a diminished sexual risk for HIV, among gay men and other MSM, especially for men in sero-different domestic partnerships or men who are employed as sex workers (31,40). New data from the U.S. has not only reinforced this point but also underscored the ongoing need for uninterrupted access to HIV prevention tools gay men and other MSM may need (13). Otherwise, consequences of the reductions in HIV prevention tools can potentially be catastrophic in the HIV prevention response, particularly if they are not reversed (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding sexual frequency with respect to the period before con nement, a decrease exists as in the study by Lehmiller et al (2020) but also an increase as in the study by Yuksel & Ozgor (2020), thus the results are inconclusive. Other studies, in line with Lehmiller et al (2020) or Sanchez et al (2020), indicate that the sexual repertoire has expanded with new activities such as sexting or viewing pornography, the use of recreational drugs and alcohol consumption. In addition, the use of dating apps would have decreased or the motivation to use them would have changed.…”
Section: Introductionmentioning
confidence: 92%
“…Speci cally, only two studies with large samples of general population have been only found, one focused on United States, Canada, the United Kingdom and Australia (Lehmiller, Garcia, Gesselman, & Mark, 2020), and another on Great Britain (Jacob et al, 2020 ). A third one also included an important number of participants from the United States although this was restricted to men who have sex with men (MSM) (Sanchez, Zlotorzynska, Rai, & Baral, 2020). The remaining of the published studies have only evaluated between 58 and 459 participants belonging to the general population from Bangladesh, India and Nepal (Arafat, Mohamed, Kar, Sharma, & Kabir, 2020), Japan (Taniguchi, Hisasue, & Sato, 2020) and a very small group of women from Italy (Schiavi et al, 2020) and Turkey (Yuksel & Ozgor, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, little has been published regarding the real impact of the need to deal with the COVID-19 pandemic and its duration on the sexual practices and loving relationships of populations (Sanchez, Zlotorzynska, Rai, & Baral, 2020), especially among LGBT populations. Few studies address the pandemic from the perspective of the quality or lack of social interactions and the role it plays in the psychological well-being of individuals by intensifying unfavorable triggers.…”
Section: Resultsmentioning
confidence: 99%